Cross-contaminations: On Schönberg's political beliefs and his music theoretical writings - Noda Haruki (Zbornik Radova Akademije Umetnosti, 2020)
This paper aims to show how Arnold Schönberg's political views permeate his theoretical writings and to a lesser degree even his musical works. Scholars usually point to works such as Ode to Napoleon Buonaparte or A Survivor from Warsaw, when discussing Schönberg's political thinking. Only seldom have scholars dealt with a more uncomfortable facet of this topic: Schönberg, for the longest time, was a convinced German nationalist. As late as 1931, ten years after the incident at Mattsee, he wrote Nationale Musik. In this short text, Schönberg tries to explain why German music is supposedly superior to that of other nations. In trying to prove his point, he uses many theoretical and analytical concepts, such as "Gedanke", "Gestalt", chromaticism, polyphony and homophony, "Themen und Sätze", "Variation und Variierung", etc. These terms and concepts are also continuously used in Schönberg's 'non-political' writings such as Harmonielehre (1911), Der musikalische Gedanke (1934-36) and Fundamentals of Composition (1937-48). This paper re-examines these texts critically and illustrates the cross-contamination between political beliefs and music theoretical thought within the writings of Schönberg.